Food allergy knowledge and training among restaurant employees. (August 2016) - Lee, Yee Ming; Sozen, Erol
Abstract: As the number of Americans with food allergies continues to increase, restaurant employees should be trained to serve customers who have this condition. This study investigated restaurant employees' food allergy (FA) knowledge and identified previous FA training, the preferred characteristics of future FA training, and the reasons why some employees were not interested in FA training. A study questionnaire was developed based on interviews with restaurateurs and previous literature and was completed by 229 restaurant employees. The results showed that the participants have some FA knowledge (20.8 ± 3.4 of 28). Many were not trained in FA but expressed interest in attending such training. The participants expressed a preference for self-paced training programs that use real-world examples and simple language. Some reasons for not being interested in attending FA training included " time consuming ", " not beneficial ", and " boring ". The restaurant industry benefits from the findings of this study by gaining a greater understanding of the current food allergy knowledge and training of restaurant employees.